Anticancer potential of Pd and Pt metallo-macrocycles of phosphines and 4, 4΄-dipyridyldiselenide. (1st January 2022) - Pal, M.K.; Wadawale, A.P.; Chauhan, N.; Majumdar, A.G.; Subramanian, M.; Bhuvanesh, N.; Dey, S.
Graphical abstract: Metallo-macrocyclic Pd II and Pt II complexes were constructed from 4, 4′-dipyridyldiselenide and wide-bite angle diphosphine dppf and Xantphos as corner ligand. X-ray analysis confirm the dimeric structure containing metal-pyridine bond. In vitro cytotoxic activity of the complexes was evaluated by MTT and clonogenic assay employing breast (MCF7), lung (A549), bone (U2OS) and ovarian (SKOV3) cancer cell lines. Induction of DNA damage by assessing γ-H2AX, showed [Pt(PEt3 )2 (4, 4′-py2 Se2 )]2 (OTf)4 has remarkably higher potential to induce nuclear abnormalities and anticancer activity than others including cisplatin. Abstract: Reactions of [M(P ∩ P)(X)2 ] (M = Pd, Pt; X = NO3, OTf) and 4, 4΄-dipyridyldiselenide yielded metallo-macrocyclic complexes [M(P ∩ P)(4, 4΄-py2 Se2 )]n (X)2n capped by wide-bite-angle diphosphines (P ∩ P = dppf, Xantphos), which were characterized by NMR spectroscopy and ESI mass spectrometry. The X-ray analysis confirm the dimeric structure of [Pt(dppf)(4, 4΄-py2 Se2 )]2 (NO3 )4 consisting of two Pt(II) centers bridged by 4, 4΄-dipyridyldiselenides holding Pt-N bonds. In vitro cytotoxic activity of the complexes along with the previously synthesized [Pt(PEt3 )2 (4, 4′-py2 Se2 )]n (OTf)2n was evaluated by MTT and clonogenic assay employing breast (MCF7), lung (A549), bone (U2OS) and ovarian (SKOV3) cancer cell lines. The results revealed the potent anticancer activity of these compounds. DNA damage was assessed by γ-H2AX, revealing that all the complexes induced DNA damage in the breast cancer cells. Further they also induced formation of micronuclei and other nuclear distortions. The complex [Pt(PEt3 )2 (4, 4′-py2 Se2 )]n (OTf)2n has induced more nuclear abnormalities and exhibited higher anticancer activity than cisplatin.